Taking Familiar Others’ Perspectives to Regulate Our Own Emotion: An Event-Related Potential Study - Lei, Yi; Wang, Yajie; Wang, Chaolun; Wang, Jinxia; Lou, Yixue; Li, Hong (Frontiers in Psychology, 2019)
Current research on emotion regulation has mainly focused on Gross’s cognitive strategies for regulating negative emotion; however, little attention has been paid to whether social cognitive processes can be used to regulate both positive and negative emotions. We considered perspective-taking as an aspect of social cognition, and investigated whether it would affect one’s own emotional response. The present study used a block paradigm and event-related potential (ERP) technology to explore this question. A 3 (perspective: self vs. pessimistic familiar other vs. optimistic familiar other) × 3 (valence: positive vs. neutral vs. negative) within-group design was employed. Thirty-six college students participated and considered their own or target others’ feelings about pictures with different valences. Results showed that positive emotional responses were more neutral under a pessimistic familiar-other perspective, and more positive under an optimistic familiar-other perspective, and vice versa for negative emotional responses. In ERP results, compared with a self-perspective, taking familiar others’ perspectives elicited reductions in P3 (370-410 ms) and LPP (400-800 ms) difference waves. These findings suggested that taking a pessimistic or optimistic familiar other perspective affects emotion regulation by changing later processing of emotional information.